Integrating climate change and energy mix scenarios in LCA of buildings and districts. (15th December 2016) - Roux, Charlotte; Schalbart, Patrick; Assoumou, Edi; Peuportier, Bruno
Graphical abstract: Highlights: A method is suggested to integrate prospective parameters in LCA of buildings. Climate change and evolution of the energy system are accounted for. Environmental assessment is performed at an hourly time step. Both climate change and evolution of the energy mix influence results. The energy use in high performance building remains an important contributor of LCA. Abstract: The objective of this study is to evaluate life cycle impacts of buildings, integrating climate change (RCP 4.5 and RCP 8.5 IPCC scenarios) and evolution of the energy mix on the long term (at 2050). Two methodological approaches were developed following the modelling principles of attributional and consequential life cycle assessment (LCA). The methodology is illustrated using a simple case study: a low-energy single family house located in France. Two design options were evaluated using life cycle assessment: the choice of a heating system and the integration of photovoltaic (PV) modules on the roof. Using an attributional approach and compared to a static LCA considering no prospective parameters, the carbon footprint of the house (total life cycle) varies from +21% to +43% for the electric heating alternative, −7% to +4% for the gas boiler alternative, −6% to +15% for the PV alternative depending on climate change intensity and evolution of the energy mix. Figures using the consequential approach have a larger magnitude of variation from −36% to −13% for the electric heating alternative, 0 to +16% for the gas boiler alternative and −14% to +1% for the PV alternative compared to a static LCA. Accounting for climate change and the evolution of the energy system has a large influence on LCA results.